2023
DOI: 10.3390/dietetics2030021
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Gastrointestinal Symptoms in Endurance Sports: A Review of Pathophysiology, Symptoms, and Nutritional Management

Emanuela Ribichini,
Giulia Scalese,
Alessandra Cesarini
et al.

Abstract: Strenuous exercise can be associated with “Exercise Induced Gastrointestinal Syndrome” (Ex-GIS), a clinical condition characterized by a series of gastrointestinal (GI) disturbances that may impact the physical and psychological performance of athletes. The pathophysiology comprises multi-factorial interactions between the GI tract and the circulatory, immune, enteric, and central nervous systems. There is considerable evidence for increases in the indices of intestinal damage, permeability, and endotoxemia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…This can be avoided by implementing strategies to ensure the inclusion of calorie-dense plant foods such as dried fruit and nut butters [46]. Furthermore, it has been suggested that the high fiber content of vegetarian diets could theoretically elicit gastrointestinal symptoms in athletes [95]. However, it has been proposed that the gastrointestinal tracts of athletes undergo adaptations that allow for larger calorie intakes through mechanisms such as increased rates of gastric emptying and nutrient absorption and reduced bloating and perceptions of fullness with greater tolerance to larger volumes of food [96].…”
Section: Discussionmentioning
confidence: 99%
“…This can be avoided by implementing strategies to ensure the inclusion of calorie-dense plant foods such as dried fruit and nut butters [46]. Furthermore, it has been suggested that the high fiber content of vegetarian diets could theoretically elicit gastrointestinal symptoms in athletes [95]. However, it has been proposed that the gastrointestinal tracts of athletes undergo adaptations that allow for larger calorie intakes through mechanisms such as increased rates of gastric emptying and nutrient absorption and reduced bloating and perceptions of fullness with greater tolerance to larger volumes of food [96].…”
Section: Discussionmentioning
confidence: 99%